ANALISIS KEVALIDAN E-BOOKLET INTERAKTIF UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SD - Izza Azzahra; Sumadi; Badri Atul Fikriyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to test the validity of interactive e-Booklet learning media developed to improve student learning outcomes. An e-Booklet is an innovative medium designed to present information through visual displays, audio, and direct interaction, thereby enhancing students' engagement and understanding of abstract material. Validation was conducted by three experts: a subject matter expert, a media expert, and a language expert, using a Likert scale-based assessment instrument. This research is a developmental study with a descriptive quantitative approach. Data collection techniques included observation sheets, questionnaires, and validation sheets. The validation results by the language expert showed a score of 89% (valid category), the subject matter expert obtained a score of 80% (sufficiently valid category), and the media expert obtained a score of 84% (valid category). The overall average validation score for the e-Booklet media was 85%, indicating that this media falls into the ‘valid’ category and is suitable for use in the learning process. Thus, the e-Booklet media meets the criteria for content, presentation, and technical aspects, and has great potential to support student learning outcomes.